Exploring mediation through creativity: ethnography, theatre and cinema with Maghrebi unaccompanied migrant youth in Barcelona - Mecca, Margot; Ballesté-Isern, Eduard (European journal of social work, 2025)
At the crossroads between artistic creation, academia and marginalised youth, we can find a space for cultural mediation through collaborative creative practices. In this article we present the ethnographic results of a fieldwork conducted in Barcelona during theatre workshops with young unaccompanied immigrants from North Africa. The workshop was an experience of personal, intra-group and intercultural mediation through creativity, during which relationships of affection and care were established that allowed for a deeper understanding of migration, daily life, personal goals, and friendship. This process developed an ethnographic approach based on collaboration between all the actors involved, characterised by a number of innovative features: a more horizontal position between researchers and research subjects; 'place' as the central axis of the ethnographic relationship; the body and affect as the ground for generating processes of trust, care and respect between those involved. Here we present findings on the methods employed and the agency of the participants, highlighting the role of theatre practices in creating conditions for non-paternalistic and non-stigmatising experiences of mediation. Finally, this ethnographic approach is of great value in working with marginalised young people: to generate better bonds of trust and space to give voice and enunciate their life situations.